The romanization of Spain - Hoyos, B; Hoyos, B. D. (1971)
This thesis treats three interconnected topics of Spanish history between 206 B.C. and Augustus: immigration from Italy, provincial and local government and the extension of civitas Romana and ius Latii to Spaniards. In different ways, these formed the framework of, and lent encouragement to, the Romanization of the Peninsula, the effects of which still endure. Though not overlooked by English-speaking scholars, Spain has not attracted attention as consistent and extensive as that accorded other lands of the Roman empire. Moreover, apart from some research by Spaniards, investigation of the period generally has tended to be particularist - concerning itself with limited problems such as Caesarian and Augustan colonization, second-century-B.C. military policy and the economic state of the country at various moments; and often occurs as part of a broader survey of conditions over several provinces (if not of the whole empire), with some loss of depth. Concentration on Spain alone, of course, can suffer from a lack of breadth and analogy, especially as paucity of evidence permanently afflicts nearly every topic in Republican Spanish history save military affairs (where it is intermittent). Yet the risk is worth taking: the problems are important as well as interesting. [Continued in text ...]